PERAN ORANGTUA KRISTIANI DALAM MEMBANGUN PENDIDIKAN KARAKTER ANAK - Natalis Sukma Permana (Bahasa Indonesia, 2019)
Parents totally have crucial role on growing up the character education in family life. From parents, the children learn the way of respecting others, loving to the diversity, respecting differences in point of view and being humble. The Catholic family is a “ecclesia domestica” (family church), the smallest part of the church. Therefore, it is not only a place of the growth and development of the Catholic faith, but also a place of strengthening the values ​​of love according to Jesus ways the eternal Teacher. Character education grows in a family life. From and within the family environment, children learn ethical values, manners, and things that are not desirable in the social environment. Along the times, the challenges of families in educating children increasingly grave. The technology advances have disrupted many dimensions of life, including the warmth in a family life.